High-glucose induced HIF-1α down-regulation impairs the function of the endothelial progenitor cells via PI3K/AKT signaling pathway. Issue 4 (2020) - Dong, Yanting; Zhou, Xiaohui; Zhang, Song; Lin, Xihua; Zhang, Nan
No abstract available